Stall-feeding beef cattle with agricultural by-products in Malawi - Butterworth, M.H.; Chintsanya, N.C.C.; Phiri, K.M.J.; Mitengo-Gama, P.W.S. (1984)
Describes operations of Malawi's stall-feeder scheme and presents 4 trial results comparing growth rate & efficiency of concentrate utilization of stall-fed beef cattle given meat-and-bone meal (MBM) and/or bone meal (BM) supplements to a 'madeya' (maize hominy feed) & poultry manure plus roughage ration w. unsupplemented ones; maize stover (MS) & groundnut haulms (GH) alone, MS & GH and madeya, or the latter supplemented with MBM & BM; and dry MS & concentrates or soaked MS & concentrates w. MBM.